A Case Study Of Students’ Ability To Speak In EFL Classroom - Lailatul Husna; Widya Juli Astria (Universitas Pahlawan Tuanku Tambusai, 2021)
In the teaching and learning of English as a Foreign Language, the active participation of students in the classroom plays an important role in acquiring the target language. The participation can be seen from the students reply to the teachers or their peers’ questions and give comments. It means that they are able to express and clarify their intentions, thoughts and opinions which are essential to language acquisition. The aim of this research is to investigate and analyze the students’ Ability to speak in EFL classroom. The method of this research is qualitative. The data were collected through the observation and and interview. The result of the research showed that 40% of the students still got anxiety in speaking. The students could not develop their skill in speaking because of the limited of their vocabulary and their grammar mastery. It is expected that this research could be beneficial for English teacher, especially to English Foreign Language teacher and lecturer who teaches English in order to find out the students’ ability in performing their speaking performance